Why does Nobody Care About the Absorption? Some Aspects Regarding Administrative Absorption Capacity for the EU Structural Funds in the Czech Republic, Estonia, Hungary, Slovakia and Slovenia before Accession - Andrej Horvat (Austrian Institute of Economic Research (WIFO), 2005)
Based on the review of literature and our own conceptual considerations, we show that absorption problems regarding the EU Structural Funds may be important. The central topic of our paper is the question of how to measure the administrative capacities of particular Candidate Countries for Structural Funds. First, we describe a suitable methodology for calculating the administrative absorption capacities of Candidate Countries. We also show that the process of preparing programming documents was the central point of the overall institution-building exercise. At the end we present calculations on administrative capacities in five Candidate Countries before their accession to the EU: the Czech Republic, Hungary, Slovakia, Estonia and Slovenia, respectively. These calculations are based on previous calculations by the European Commission and on the strategic documents negotiated between the Commission and these Candidate Countries before the end of 2003. By calculating the key indicators of administrative capacity, we offer some preliminary statements regarding the administrative capacity in a particular new Member State and provide additional information on the overall absorption capacity of the countries in the 2004-2006 programme period. However, by first Annual Implementation Reports already being produced by new Member States in July 2005 this paper remains just a work-in-progress.
Keywords: 330; Estonia; Hungary; Slovakia and Slovenia before Accession; EU-Strukturfonds; Tschechien; Estland; Ungarn; Slowakei; Slowenien